Compressive load comprising 70% natural aggregate (NA) 30% crushed concrete wasted aggregate (CCwA) / Abdul Allim Abdul Rashid - Abdul Rashid, Abdul Allim (Faculty of Civil Engineering, 2012)
Reinforced concrete walls have gained greater acceptance in many countries in conjunction with the Industrialized Building System (IBS). As part of the development of an industrialized housing method, wall panels are designed and tested. This experimental research of structural behaviour of short waii panei under axial ioad comprising 70% Natural Aggregates and 30% Crushed Concrete Wasted Aggregates was carried out. The wall samples reinforced with one layer steel fabric size B7 and concrete Grade 30. The 150 mm x 150 mm x 150 mm concrete cubes were cast for 100% NA and another 30% CCWA and 70% NA to determine the compressive strength. Two samples of short wall panel of sized 75 mm x 500 mm x 1000 mm (Width : Height: Length) were tested under compressive load to determine the ultimate load and structural behaviour. From the analysis , it shows that ultimate load from mixing 70% NA and 30% CCWA at 115 kN. Mode of failure short wall panel are crushing.